1995
DOI: 10.1177/0022002795039004006
|View full text |Cite
|
Sign up to set email alerts
|

High And Low Trusters' Responses To Fear in a Payoff Matrix

Abstract: Interpersonal trust has long been known to influence cooperation. This study tested the hypothesis that one's degree of trust in others will influence the extent to which one reacts to the presence of fear (or the possibility of receiving no payoff for cooperative actions) in a payoff matrix. The hypothesis was formally tested with public goods games and resource dilemma games, with fear manipulated. Results support the hypothesis: when fear was present, high trusters cooperated more frequently than low truste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(76 citation statements)
references
References 16 publications
3
72
0
Order By: Relevance
“…Parks et al (1995Parks et al ( , 1996 also uses the Yamagishi SVO scale to look for correlation between people's trust score and their behavior in social dilemma situations. Parks and Hulbert (1995) investigate the effects of trust on subjects' response to fear in a social dilemma. They find (among other things) that high trusters cooperate more than low trusters when fear was present but cooperate at the same rate when fear is absent.…”
Section: Discussion Of Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parks et al (1995Parks et al ( , 1996 also uses the Yamagishi SVO scale to look for correlation between people's trust score and their behavior in social dilemma situations. Parks and Hulbert (1995) investigate the effects of trust on subjects' response to fear in a social dilemma. They find (among other things) that high trusters cooperate more than low trusters when fear was present but cooperate at the same rate when fear is absent.…”
Section: Discussion Of Our Resultsmentioning
confidence: 99%
“…This preserves the one-7 This trust scale was originally developed by Yukawa (1985) based on the factor analysis of 60 items related to trust. 8 See Yamagishi (1986) and Yamagishi and Sato (1986) 9 See Parks et al (1995Parks et al ( , 1996 10 (1) Most people tell a lie when they can benefit by doing so. The game started with each subject making a Player 1 decision.…”
Section: Sequential Game Overviewmentioning
confidence: 99%
“…A prevalent reason not to contribute to a public good dilemma consists of the fear that one's resources are wasted if others refrain from contributing (Parks & Hulbert, 1995;Rapoport & Eshed-Levy, 1989). …”
Section: Methodsmentioning
confidence: 99%
“…The interactive effect between facial displays of emotions and verbal communication In the context of social dilemma situations, issues of trust are important, because they promote cooperation (De Cremer, Snyder, & Dewitte, 2001;Parks & Hulbert, 1995) and, important for the present research, people's willingness to trust explanations and promises of other group members (Shapiro, 1991;Tomlinson, Dineen, & Lewicki, 2004). Indeed, recent research has shown that if people trust the other person, they perceive this person as more honest and are more likely to take into account the other person's verbal communication (Tomlinson et al, 2004).…”
Section: Emotion Displays and Inferences Madementioning
confidence: 99%